INTERPRETASI DAN KARAKTERISTIK METODOLOGI PENAFSIRAN DALAM SURAT AL-MA'UN DALAM KITAB TAFSIR NAZM AL-DURAR FI TANASUB AL-AYAT WA AL-SUWAR KARYA Al-BIQA'I - Setiyawan, Said Ali; Tarto, Tarto; Khoirunnisa, Khoirunnisa (IAINU Kebumen Prodi IAT, 2023)
This research aims to explore the meaning behind the interpretation of Surah Al-Ma'un and trace the characteristics of the interpretive methodology used by Al-Biqā'ī in his tafsir book. The choice of al-Ma'un's letter was based on the author's interest in the relationship between spiritual and social piety contained in it. This book has a unique character in interpreting the Al-Qur'an in the form of a paradigm of systematic harmony of the Al-Qur'an. The method used to trace the characteristics of interpretation is the model of mapping tafsir books offered by Walid Saleh in the form of encyclopedic, madrasah and hasiyah model interpretations. In exploring or analyzing the meaning contained in Surah al-Ma'un, the author compares it with the words contained in other letters. The author uses a research subject content approach to further analyze the two main problems of this research. The data obtained was processed using descriptive analysis techniques. This research confirms that, firstly, spiritual piety does not have significant meaning if it is not balanced with spiritual piety. Second, in interpreting al-Ma'un's letter, Al-Biqā'ī's interpretation is in the madarasah model of interpretation.